2015
DOI: 10.1002/mrc.4327
|View full text |Cite
|
Sign up to set email alerts
|

Through‐space 19F–19F spin–spin coupling in ortho‐fluoro Z‐azobenzene

Abstract: We report through-space (TS) (19)F-(19)F coupling for ortho-fluoro-substituted Z-azobenzenes. The magnitude of the TS-coupling constant ((TS) JFF ) ranged from 2.2-5.9 Hz. Using empirical formulas reported in the literature, these coupling constants correspond to non-bonded F-F distances (dFF) of 3.0-3.5 Å. These non-bonded distances are significantly smaller than those determined by X-ray crystallography or density functional theory, which argues that simple models of (19)F-(19)F TS spin-spin coupling solely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(75 reference statements)
0
8
1
Order By: Relevance
“…There is only one literature report on the experimental determination of phenyl rotation barrier in E -AB and none for Z -AB. We have previously reported through-space 19 F– 19 F coupling for o -fluorosubstituted Z - AB . In this study, we combine theory and variable-temperature NMR to determine the phenyl rotation barrier in Z -AB systems.…”
Section: Introductioncontrasting
confidence: 59%
See 2 more Smart Citations
“…There is only one literature report on the experimental determination of phenyl rotation barrier in E -AB and none for Z -AB. We have previously reported through-space 19 F– 19 F coupling for o -fluorosubstituted Z - AB . In this study, we combine theory and variable-temperature NMR to determine the phenyl rotation barrier in Z -AB systems.…”
Section: Introductioncontrasting
confidence: 59%
“…Six compounds are the subject of the present study (Scheme ). Synthesis and characterization of these compounds has been previously reported …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The most cogent advice I received during this correspondence was “fluorine NMR can be really tricky.” For this special issue of the Journal of Physical Organic Chemistry , I have chosen to summarize this project, which J.D.R., once again, made me solve myself (a hallmark of his training). Portions of this study have been published previously . The succinct summary of this project is that we measured the barrier to phenyl rotation in a metastable Z ‐azobenzene using the temperature dependence of through‐space (TS) 19 F‐ 19 F spin‐spin coupling.…”
Section: Roberts' Mentorshipmentioning
confidence: 99%
“…Compounds used in this study are shown in Scheme 1. The synthesis of 4-6 has been reported [12], 1, 2, 8, 10 are commercially available and 3 was prepared in a conventional manner by the Mills reaction [5]. Compounds 10 and 8 are reagents in a collagenase assay [13].…”
Section: Solubilitymentioning
confidence: 99%